Case report: Behavioral variant FTD confounding a language variant FTD in a case of PSP-CBS - Jürs, Alexandra V.; Kasper, Elisabeth; Neumann, Manuela; Kurth, Jens; Krause, Bernd J.; Cantré, Daniel; Prudlo, Johannes (Frontiers in Dementia, 2025)
Frontotemporal dementia (FTD) occurs in two main clinical subtypes, which can transition into one another: the behavioral variant (bvFTD) and the language variant (primary progressive aphasia; PPA). It is common for the latter, as primary progressive aphasia (PPA), to transition into bvFTD; however, the opposite development, where bvFTD is followed by “secondary progressive aphasia,” has received little attention. This constellation is particularly challenging to recognize as frontal dysexecutive syndrome can confound subsequent progressive aphasia as impulsive behavior, a lack of inhibition, and apathy can lead to non-aphasic communication disturbances, including impoverished syntax, reduced cognitive flexibility, and insufficient error monitoring. A 78-year-old patient, with a disease duration of 10 years, was initially diagnosed in the 3rd year of the disease with corticobasal syndrome (CBS) with frontal behavioral-spatial syndrome (CBS-FBS) and subsequently with CBS with progressive non-fluent aphasia (CBS-PNFA) in the 4th year. Severe ophthalmoplegia was the reason for changing the diagnosis in the seventh year to progressive supranuclear palsy with CBS predominance type (PSP-CBS). The pathological diagnosis was FTLD-tau in the form of a PSP subtype. The MRI showed asymmetric atrophy, particularly of the left insular cortex and the left inferior frontal gyrus. The 2-[18F]FDG-PET revealed left-accentuated bifrontal glucose hypometabolism. This case report highlights how progressive neurodegenerative aphasia can occur in FTD not only as a primary language phenomenon (in the sense of PPA) but also as a secondary phenomenon (following a primary behavioral disorder with a non-aphasic communication disorder). Dysexecutive syndrome can mask aphasia. Therefore, incorporating spontaneous speech tasks into standard neuropsychological language tests, in addition to MRI and PET imaging techniques, could help better recognize such secondary aphasias, even in the presence of dysexecutive syndrome, and thus broaden our understanding of the natural history of FTD.